Núcleos de acessibilidade nas Instituições Federais de Ensino Superior de Minas Gerais: acesso, permanência e conclusão dos acadêmicos surdos - Cipriano, Patrícia Silva (2022)
The school inclusion of students with disabilities is a recurring theme in academic debates, mainly about the advantages and disadvantages of the proposed incorporation of the same in the educational space. Although there are governmental and legislative efforts in this direction and pretensions to guarantee the right of people with disabilities to education, at all levels of schooling, the area of special education faces different positions and divergent reflections. This research focuses on the performance of the Accessibility Centers (NA) of the Federal Institutions of Higher Education (IFES) in favor of the inclusion of deaf students. As a research problem, we seek to understand what are the contributions of the NA of the IFES of Minas Gerais in the formation of deaf students? It starts from the hypothesis that the NA are fundamental for the educational inclusion of the deaf student in higher education in the IFES of Minas Gerais and develop a work of great importance for the academic training success of deaf students. We established as a general objective to understand the performance of the Accessibility Centers in the implementation of educational inclusion policies within the IFES and their contributions to the training process of deaf students. More specifically, we intend to: understand some aspects related to the educational process of the deaf student in higher education; to describe the history of the creation, institutionalization and performance of the NA within the scope of the IFES, as well as to identify the attributions of the NA to implement institutional policies for the inclusion of deaf students and to analyze the impact of the actions of the NA in the educational processes of deaf students in the IFES of Minas Gerais. This research is characterized by a qualitative, exploratory approach of a basic nature, developed through a bibliographic research to survey the theoretical framework, based on the authors: Quadros (2004), Mendes (2006), Castilho (2008), Gadelha (2009), Mazzotta (2011), among others, in addition to several documents concerning the current legislation on accessibility and inclusion of people with disabilities (PwD), and especially aimed at the deaf. A field research was also carried out with the Accessibility Centers of the IFES of Minas Gerais through the application of an online questionnaire to the coordinators of these centers, in order to obtain information on the actions taken to guarantee the access, permanence and completion of deaf people. , respecting the time frame between 2008 and 2019. A survey of the theoretical framework was carried out, a first collection of preliminary information and later we applied a second data collection through an online questionnaire to the coordinators and data analysis was carried out from the methodological proposal of Bardin's content analysis (2011). The discussion of the research results was developed from the Foucauldian framework, based on the analysis of the inclusive process from the perspective of biopolitics and governmentality. The research has shown that the inclusion of deaf students in higher education has increased considerably as a result of the growing number of enrollments of people with disabilities in Basic Education. Our research evidenced the existence of 17 Federal Institutions of Higher Education in Minas Gerais and, of these, 14 informed that they have Accessibility Centers in activity.